Antiangiogeneic Activity of Annona Reticulata Seeds Extract - Bahir Abdul Razzaq Mshimesh; Israa falah Hassan; Ahmed Majeed Al-Shammari (Iraqi Journal of Cancer and Medical Genetics, 2022)
Background: Annona reticulata used in traditional medicines for epilepsy, dysentery, constipation, cardiac problems and asinsecticide. Annona reticulata seeds extracts contain active acetogenins compounds.Aim of study : The study aimed to investigate the possible antiangiogenic activity of Annona reticulata extracts.Material and method: The sequential extraction process with two solvents used to extracts grinded seeds of A. reticulata in thefollowing order according to increment in polarity: n-hexane and ethanol.CAM assay and Ex-vivo rat aorta assay was used toidentify the antiangiogeneic activity of both extracts and determine the most biological active extract.Results: According to CAM assay, there was a statistically higher percent of inhibition zone during exposure to bevacizumab and the two extracts of A. reticulata at both concentrations when compared with DMSO, as a negative control group(p-value ≤ 0.05). Meanwhile, n-hexane extract at only higher concentration (500 µg/5µl) showed a significantly greater zoneof inhibition compared with bevacizumab group (p-value ≤ 0.05).Data of rat aorta rings assay that represented as mean ofblood vessels growth inhibition revealed a statistically higher percentage of inhibition in bevacizumab and both extracts of A.reticulata treated group compared with negative control group (p-value ≤ 0.05). In this study, the percent of growth inhibitionafter exposure to n-hexane was approach to that of bevacizumab, where no significant difference was observed between bothgroups (p-value > 0.05), while group that treated with ethanol extract showed statistically lower percent of growth inhibitioncompared with n-hexane and bevacizumab treated groups (p-value ≤ 0.05). The results of this assay for the five concentrationsof ethanol and n-hexane extract showed a significant reduction in blood vessels growth in a concentration- dependent manner(P ≤ 0.05) compared with negative control. The IC50, n-hexane was 74.95µg/ml while the value of IC50 for ethanol 95.89